STRATEGY OF GREEN DESIGN IMPLEMENTATION FOR OPTIMIZING OF THE NATURAL VENTILATION AT HIGH-RISE BUILDING - Juliana Bekti Susilaning Budi; Khairunnisa Fifthariski; Sri Yuliani; Wiwik Setyaningsih (ARSITEKTURA, 2018)
The natural air conditioning in the medical school building hall of the Faculty of Medicine, Universitas Sebelas Maret needs to be optimized in order to achieve maximum thermal comfort. Optimal natural stability with the support of green space within a building can increase the level of comfort that supports user activity. The purpose of the research is to optimize the natural system applied in the building that is on the void located in the middle of the building by providing green space placed on the hall of the building so as to provide maximum thermal comfort on the user building according to principles in architectural design . This research used qualitative method based on literartur study, field observation and interview result with user of doctor building of Faculty of Medicine, Sebelas Maret University. The expected result from the provision of green space in the hall space of the building is the optimal natural innate in the building so that the building users feel comfortable in the move.